Shakespeare for all Seasons ? Richard II en Avignon : de Jean Vilar (1957) à Ariane Mnouchkine (1982) - Isabelle Schwartz-Gastine (Revue LISA)
Richard II has not often been performed on the French stage; however, in the 20th century, within a period of 35 years, two productions premiered at the same venue (the Cour d’Honneur at the open-air Avignon Festival), were so successful that they became emblematic of their times. In 1947 Jean Vilar opened the first Avignon Festival with an ascetic, charismatic eponymous hero who came to an inner knowledge of himself in his bare prison cell; in 1982 Ariane Mnouchkine offered a splendid visual display by transposing the play into the kabuki tradition; this offered the audience breath-taking and dynamic tableaux of elaborate court ceremonies and rebellious lords.At such a distance in time, the English medieval code of honour was dealt with according to completely different theatrical principles of ethics and aesthetics, mirroring the changes in perspective within French society.